Compensating Wage Differentials and the Endogeneity of Job Riskiness - Garen, John (The Review of Economics and Statistics, 1988)
Those with greater earnings capacity are likely to choose safer jobs, assuming safety is a normal good. Those who e xperience greater returns to job may choose riskier jobs. This paper estimates wage premia for risk of fatality and injury, allowing unobs ervables to affect earnings capacity and the returns to risk. As the endogeneity of job risk causes bias in OLS estimation, the model is e stimated with simultaneous equations and modified selection bias tech niques. The results indicate that unobserved heterogeneity in the ret urns to risk is important and that OLS underestimates the wage premia for fatality and injury risk. Copyright 1988 by MIT Press.